A short communication regarding the trends and prevalence of H. Pylori in unselected gastric mucosal biopsy samples at a tertiary care hospital in Karachi, Pakistan: a five-year retrospective - Ahmed, Naseem; Zameer, Sambreen; Ghazanfar , Shamas; Islam , Zarmina; Jatoi, Hafsa Nazir; Khan, Manal (Journal of the Pakistan Medical Association, 2024)
A spiral gram-negative bacteria, known as helicobacter pylori, is frequently discovered in the stomach and is linked to a number of clinical disorders. Understanding its prevalence and trends is crucial for both improved clinical outcomes as well as greater epidemiological insight into the region. The current retrospective study was planned to analyse the prevalence and frequency trends of helicobacter pylori in gastric mucosal samples from a Karachi-based tertiary care centre. Data from a 5-year period was analysed. Sampled individuals' age, gender, site of infection and histopathological findings were noted. A decreasing trend in helicobacter pylori infections in biopsy samples was observed. Gender and age showed no significant association (p>0.05), while infection site and histopathological findings exhibited significant correlations (p<0.05). Antrum predominated for all types of gastritis. The study highlighted a declining trend in helicobacter pylori prevalence in Karachi over 5 years. Further multicentre studies with larger samples may provide deeper insights into helicobacter pylori trends in Pakistan. Key Words: Gastritis, Antrum, H. Pylori, Gastric ulcer.